2007
DOI: 10.1111/j.1398-9995.2007.01526.x
|View full text |Cite
|
Sign up to set email alerts
|

The functional insufficiency of human CD4+CD25high T‐regulatory cells in allergic asthma is subjected to TNF‐α modulation

Abstract: The functional insufficiency of nTreg cells in patients with allergic asthma may be related to the enhanced production of TNF-alpha and its effect on the Foxp3 expression. These results may explain, in part, the effectiveness of anti-TNF-alpha therapy in the treatment of allergic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
92
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 34 publications
(44 reference statements)
8
92
1
1
Order By: Relevance
“…T reg function has also been shown to be defective in collagen-induced arthritis (CIA) [119] and there is also evidence from other diseases that TNF-a compromises the activity and/or numbers of T reg cells. For example, deficient suppressor cell activity was observed in human CD4 + CD25 + T reg in allergic asthma and this deficiency could be corrected by TNF-a blockade [132]. Similar conclusions were reached in EAE [133], MS [134] and type 1 diabetes [135].…”
Section: Cd25mentioning
confidence: 57%
“…T reg function has also been shown to be defective in collagen-induced arthritis (CIA) [119] and there is also evidence from other diseases that TNF-a compromises the activity and/or numbers of T reg cells. For example, deficient suppressor cell activity was observed in human CD4 + CD25 + T reg in allergic asthma and this deficiency could be corrected by TNF-a blockade [132]. Similar conclusions were reached in EAE [133], MS [134] and type 1 diabetes [135].…”
Section: Cd25mentioning
confidence: 57%
“…that express the highest density of CD25 in human (Lin et al 2008). The quality or quantity of CD4 + CD25 high Tregs from peripheral blood of patients with active SLE was significantly decreased as compared with normal donors and patients with inactive SLE (Valencia et al 2007;Bonelli et al 2009;Cai et al 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that oral administration of LAB induces CD4 + CD25 + Foxp3 + regulatory T cells, which suppress allergic disorders such as asthma or food allergy (39,40). In Peyer's patches and spleen, these cells cause suppression of IgE production (41).…”
Section: Discussionmentioning
confidence: 99%